Level Of Public Trust In The Economic Census And Its Impact On Increasing The Accuracy Of Decil Determination For Public Welfare - Nur Indah Rahmawati (Journal of Creative Power and Ambition (JCPA), 2026)
The 2026 Economic Census (SE 2026) is a national data collection initiative serving as the foundation for updating the National Socio-Economic Single Data (DTSEN), which is used to classify the population's welfare levels into ten deciles. However, its implementation faces challenges regarding public resistance and low trust, potentially compromising data accuracy and the precision of decile assignments. This study aims to measure public trust in SE 2026, identify its determining factors, and analyze its impact on the accuracy of welfare decile classification. Employing a mixed-methods approach—comprising a survey of 100 respondents in the Kemandungan area of ​​Tegal City and in-depth interviews with 20 key informants—the study finds that public trust levels range from low to moderate. Dominant factors influencing this include concerns regarding data confidentiality, taxation issues, and the fear of losing access to social assistance. Analysis reveals a significant causal link between low trust and data inaccuracy, which in turn leads to errors in decile classification and the mis-targeting of social assistance programs. The study recommends strengthening inclusive public communication strategies, engaging local figures, and ensuring transparency in data management to build public trust and facilitate the implementation of well-targeted policies.